1996
DOI: 10.1097/00004728-199601000-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Computerized Approach for Morphological Analysis of the Corpus Callosum

Abstract: The proposed methodology utilizes the full resolution of the data, rather than relying on global descriptions such as area measurements. The application of this methodology to an elderly group indicated sex-related differences in the callosal shape and size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
205
1
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 293 publications
(214 citation statements)
references
References 14 publications
3
205
1
5
Order By: Relevance
“…Jacobian determinant values derived from these tensor fields indicate the fractional volume expansion and contraction at each voxel (e.g., Chung et al, 2001;Davatzikos et al, 1996). In other words, the resulting Jacobian map quantifies the magnitude of regional volume alterations required to match the template.…”
Section: Image Analysismentioning
confidence: 99%
“…Jacobian determinant values derived from these tensor fields indicate the fractional volume expansion and contraction at each voxel (e.g., Chung et al, 2001;Davatzikos et al, 1996). In other words, the resulting Jacobian map quantifies the magnitude of regional volume alterations required to match the template.…”
Section: Image Analysismentioning
confidence: 99%
“…Therefore, measuring volumes or average PET signals of a few structures cannot capture Voxel-based morphometry (VBM) has been proposed by a number of investigators as a more comprehensive way of measuring the spatial distribution of brain atrophy in MCI and AD, by evaluating images region by region instead of making a priori assumptions about specific ROIs. A variety of VBM-type methods exist (Ashburner and Friston, 2000;Chung et al, 2001;Davatzikos et al, 2001;Davatzikos et al, 1996;Thompson et al, 2001), which generally fall under the umbrella of the field of computational neuroanatomy (Ashburner et al, 2003;Miller et al, 1997). VBM studies have confirmed that complex spatial patterns of brain atrophy can be measured in MCI and AD (Bozzali et al, 2006;Chetelat et al, 2002; Davatzikos et al, in press, 2006;Karas et al, 2004;Pennanen et al, 2005a;Saykin et al, 2006;Thompson et al, 2001;Whitwell et al, 2007;Xie et al, 2006).…”
mentioning
confidence: 99%
“…This global transformation consists of a rigid component describing the patient positioning, and the remaining non-rigid components describing the global and local shape differences between each subject and the reference anatomy. To examine the shape differences only we take the approach of Davatzikos [7] and Machado [17] and examine the differential properties of the spatially normalising transformation through the Jacobian matrix, …”
Section: Clinical Hypothesis For Shape Differences In Ad and Ftldmentioning
confidence: 99%
“…To remove the influence of brain size from the analysis we have chosen to scale each Jacobian value by the average Jacobian of the subject. To detect differences in shape of the distributions for AD J RA (x), SD J RS (x) and FTD J RF (x) from the control group J RC (x) at each point, we have used the effect size as employed by Davatzikos et al [7] and Machado et al [17], defined between the AD and control group as:…”
Section: Clinical Hypothesis For Shape Differences In Ad and Ftldmentioning
confidence: 99%
See 1 more Smart Citation